Thermal and morphological properties of PVA/4-vinylbenzene boronic acid hybrid nanofibrous - KAHRAMAN, MEMET VEZİR (WILEY, 2012)
The aim of this study was to investigate the preparation and characterization of PVA and PVA/4-VBBA (4-Vinylbenzene boronic acid) hybrid electrospun nanofiber mat. PVA was mixed with cross-linkable 4-Vinylbenzene boronic acid (4-VBBA), enabling the polymer to cross-link upon UV irradiation. The photo-cross-linking reaction was characterized by a Fourier transform infrared spectroscopy. The structure and morphology of electrospun membranes were investigated by scanning electron microscopy (SEM). SEM images showed that the nanofiber diameter and the nanostructured morphology depended on solution viscosity, applied electric voltage(AV), tip to collector distance (TCD), and the amount of the 4-VBBA. The thermal properties of PVA and PVA/4-VBBA hybrid nanofibers were investigated by thermo gravimetric analysis. The photo-crosslinked nanofibers were insoluble in water. POLYM. COMPOS., 2012. (c) 2012 Society of Plastics Engineers
Keywords: POLY(VINYL ALCOHOL); BLEND NANOFIBERS; POLYMER NANOFIBERS; FABRICATION; COMPOSITE; MATS; PVA